Prominent fin-contributed swimming in squid (Loligo forbesii) supports efficient movement in seamount habitats - Seth Cones; Nathan Formel; Jorge Fontes; Pedro Afonso; K. Alex Shorter; Gonçalo Graça; C. Robert Priester; Diya Das; T. Aran Mooney (Royal Society Open Science, 2025)
Animal movements and the associated energy costs dictate an individual’s scope for activity and habitat use. Yet in situ measurements of movement often fail to quantify whole-body movement and their physiological costs. These challenges lead to data gaps connecting how movement behaviours and energy output interact to constrain species’ biogeography. Here we combined swim tunnel respirometry and multi-positional field biologging data to estimate the energy output of squid (Loligo forbesii), an ecologically key marine invertebrate. Laboratory respirometry experiments revealed a strong correlation between body mass and metabolic rate during fin-contributed swimming, enabling energy cost estimates in the wild. Free-ranging squid enacted dynamic and diverse fin and jet swimming that varied on short time scales. Animals largely selected (66%) low-amplitude fin-contributed movements where fin waves propagated metachronally. Higher amplitude fin and jet movements were rare, accounting for 4% of time budgets. Application of the bioenergetic model on naturally exhibited behaviours estimated that animals consumed 3117 ± 532 mg O2 per day to fuel the predominant metachronal fin movements, an expenditure energetically comparable to that of similar-niche fishes. These unique data reveal substantial behavioural flexibility and indicate squid prefer low-cost movement behaviours that may enable squids’ high growth rates and successful competition with fishes.